Transnacionalidade e História de Vida: Uma mulher hindu de regresso a Maputo - Rita Ávila Cachado (Cadernos de Estudos Africanos)
Contemporary history of East Africa is linked with the history of West South Asia through trade and through social mobility, in a geographic, historical and cultural linkage.This paper follows a trend in transnational studies to incorporate life histories in order to thicken our knowledge. It recounts the story of a Hindu woman that migrated from India to Mozambique, from Mozambique to Portugal and from there to the United Kingdom. Twelve years after leaving Mozambique, M. went back to Maputo where she visited old friends and relatives. While M. was living in Portugal and in the UK, the African axis of the Portuguese Hindu-Gujarati diaspora seemed to have been forgotten; however, when she revisited places and social contexts where she had lived before, this axis was revived with old and new meanings.